0280 Occupational risk factors for prostate cancer: a case-control study in Guadeloupe (French West Indies). (23rd June 2014) - Morvan, Karène; Multigner, Luc; Blanchet, Pascal; Luce, Danièle
Abstract : Objectives: To study the associations between occupation, industry and prostate cancer risk in Guadeloupe, a high incidence area. Method: Incident cases of prostate cancer (707 cases) and 722 population controls were included. Information on lifetime occupational history and other potential risk factors was collected by interview. Logistic regression was used to estimate adjusted odds-ratios (OR) and their 95% confidence intervals (CI). Results: A significantly decreased risk was observed in farmers (OR=0.5; CI 0.4–0.7), whereas marginally elevated ORs were found for farm workers, especially in sugarcane and banana farming. Banana plantation workers had been exposed to chlordecone, an estrogenic insecticide previously found to be associated with prostate cancer risk in this population. Significantly increased risks of prostate cancer were found in stock clerks (OR=2.7; CI 1.0–7.2), fishermen (OR=2.0; CI 1.0–4.0), mail distribution clerks (OR=7.7; CI 1.7–34.4) and electricians employed for more than 20 years (OR=4.0; CI 1.0–15.8), as well as in public administration (OR=1.8; CI 1.2–2.9), retail trade (OR=2.6; CI 1.1–6.0) and manufacture of food products (OR=2.0; CI 1.1–3.9), particularly sugar (OR=13.2; IC 1.6–108). Non-significantly elevated ORs were also seen for construction workers and transport equipment operators. Conclusions: Although the overall findings suggest that occupational factors have only a limited role in prostate cancer aetiology, elevated risks of prostate cancer were found in several occupations or industries. Exposure to pesticides, solvents, traffic-related air pollution, low physical activity, whole-body vibration may explain some of these increased risks.